FONTES PARA A HISTÓRIA ECLESIÁSTICA DOS CAMPOS GERAIS (Revista de História Regional, 2007)
The project did not aim any action towards onespecific community, but to safeguard, through technicalprocedures, the documents produced by the Congregação doVerbo Divino since it came to Ponta Grossa, in 1903, to thepresent. Besides the internal documents, the collection iscomposed of newspapers and other periodical collections,books, pamphlets, reports, minutiae and annals of nationalmeetings, catalogs, photographies, etc. The large amount ofmaterial was kept by Seminário Verbo Divino, which was aprovisory headquarter for the SVD and, so, centralized thearchives foo all the written materials regarding thecongregation. The project allows History students to put into practice the theoretical knowledge acquired in the respectiveundergraduate disciplines dealing with archives, museumsand historical heritage.